An exploration into the desired characteristics of marketing graduates entering the South African retail industry: a survey-based, quantitative, cross-sectional study. - Coetzee, Quintin (The IIE, 2016)
The South African economy is experiencing slow growth, which has a direct impact on the retail industry. For marketing graduates, finding a job in the South African retail industry is a highly competitive endeavor, and marketing students should therefore ensure that they prepare themselves in the best way possible to enter the industry whilst still at university. The purpose of this research study is to determine the desired characteristics – specifically work experience, education and abilities, and personality traits – of marketing graduates entering the retail industry in South Africa, so as to equip marketing students with the necessary knowledge they to better prepare themselves for their entrance into, and finding employment in, industry upon graduation, and better position themselves for success in their careers. With the current amount of research into the matter of desired graduate characteristics within the South African retail industry being relatively low, the amount of such valuable information available to marketing students is limited, further fueling the motivation behind this research study. The researcher gained a comprehensive understanding of the existing literature that relates to the topic of the study, which, as part of a literature review, provides a solid background upon which this research study is based. A cross-sectional, quantitative approach was used for this study, which is exploratory in nature, and the falls under the critical realist paradigm. Data was obtained by means of a number of self-administered surveys sent to marketing and branding professionals at a variety of retail corporations in Cape Town, South Africa, over a period of weeks in mid-2016. Once the data was received and summarized, the researcher conducted a statistical analysis, attempting to identify patterns and trends in respondent answers. As a result of a thorough analysis of the data, and after the results were interpreted, certain findings were determined as part of this study, thus identifying the desired characteristics, amongst South African retail marketing professionals, of marketing graduates entering the South African retail industry. The findings were grouped in terms of survey question type, detailed, and represented in the form of bar graphs and frequency tables. The reliability, validity, and ethicality of this study were considered by the researcher before the research was conducted. While the study does have limitations, through its findings, it is able to contribute towards the broader body of knowledge about the South African marketing industry, and graduates entering the retail industry.
Keywords: Marketing graduates; Graduate characteristics; Retail industry